Steam System Optimization of an Industrial Heat and Power Generation Facility - Kitanovski D., Lazarevska A.M., Mladenovska D., Filkoski, R.V. (SDEWES, 2019)
Improvement of the energy conversion processes efficiency helps achieving more reliable energy supply, cleaner environment, more competitive businesses and higher living standard. Data from industry shows that there is a significant potential for efficiency enhancement of steam systems and minimization of their operating costs by implementing various opportunities and measures. The present work is a result of a system approach for energy performance analysis and identification of opportunities for optimizing the steam and condensate system of the combined heat and power plant ELEM Energetika, located in Skopje, R. N. Macedonia. The boiler plants provide superheated steam, which is further used (1) for hot water preparation intended for the local district heating system and (2) as process steam for industrial customers. Since the main plant operational cost is the one for natural gas consumption, implementing a set of energy efficiency measures shall lead to its reduction, accompanied with reducing the overall negative impact on the environment. As a result of a systems approach analysis a number of energy efficiency opportunities have been identified. For each of the measures considered, the impact on certain/separate parts of the system, as well as on the system as a whole, is analyzed using the Steam System Modeler Tool (SSMT). This paper elaborates only some of the identified opportunities, which are considered most viable from an operational and practical point of view, focused mostly on the steam generation for district heating. Based on the conducted analysis, estimated were the energy and financial savings that shall derive from implementing the elaborated measures, showing significant potential for improvement.
Keywords: Energy, boiler plant, steam system optimization, combustion, efficiency improvement